Persepsi Manfaat dan Persepsi Resiko Terhadap Penggunaan Digital Payment dengan Trust Sebagai Variabel Mediasi Studi pada Desa Se Kabupaten Tegal - Alfian, Mohammad; Widodo, Nova Maulud (Owner : Riset dan Jurnal Akuntansi, 2024)
Interest in Using Digital Payments with Trust as Mediation. This type of research is descriptive with a quantitative approach and data collection techniques using a questionnaire. The population used is all village officials in Tegal Regency, the sampling technique is purposive sampling with the criteria of all village officials in Tegal Regency knowing operational transactions at Balaidesa. Partial Least Square (PLS) analysis method with SmartPLS version 3.0 by testing the values of Convergent Validity, Discriminant Validity, Composite Reliability, Bootstrapping. The results were (1) The perceived benefits have a positive and significant effect on the interest in using digital payments. (2) Perceived risk had a negative effect on interest in using digital payments. (3) Trust had a positive and significant effect on interest in using digital payments. (4) Trust succeeded in mediating the effect of some perceived benefits on interest in using digital payments. (5) Trust had succeeded in fully mediating risk perceptions of interest in using digital payments.